RASIONALITAS KEIKUTSERTAAN ORANG TIONGHOA PADA PERAYAAN BULAN RAMADHAN DI KECAMATAN KRIAN KABUPATEN SIDOARJO - Fihtri, Elvira; Fauzi, Agus Machfud (Universitas Tanjungpura, 2022)
This study aims to determine the rationality of the participation of the Chinese in the celebration of the month of Ramadan in Krian District. According to Max Weber that individuals in carrying out social actions have a specific purpose and rational considerations. Rationalization is important before someone acts. Rationalization is simply defined as all possible considerations made by the Chinese before finally doing or acting in participating in the celebration of the Month of Ramadan. This study uses a qualitative method. The results of this study found that the actions of the Chinese were aimed at maintaining good relations between fellow religious communities, respecting Muslims who accepted the existence of the Chinese as ethnic minorities in Krian, and as social capital for the Chinese in the Krian community. These actions are carried out consciously, through social activities as a means or means of achieving the desired goals. The actions of the Chinese are also based on the rationality of social values and religious values. In addition, the actions of the Chinese are also based on reciprocal feelings and the behavior of the Javanese who are identical with helping, like to give in, so that there is no hostility. Because, even though they have Chinese ancestry, they have lived in Java for quite a long time. So often the daily actions of the Chinese are accustomed to the behavior of the Javanese.